Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1165/rcmb.2006-0419oc
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of IL-13–Induced iNOS-Derived Gas Phase Nitric Oxide in Human Bronchial Epithelial Cells

Abstract: Exhaled nitric oxide (NO) is altered in numerous diseases including asthma, and is thought broadly to be a noninvasive marker of inflammation. However, the precise source of exhaled NO has yet to be identified, and the interpretation is further hampered by significant inter-subject variation. Using fully differentiated normal human bronchial epithelial (NHBE) cells, we sought to determine (1) the rate of NO release (flux, pl.s(-1.)cm(-2)) into the gas; (2) the effect of IL-13, a prominent mediator of allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 47 publications
(58 reference statements)
7
73
0
2
Order By: Relevance
“…There were previously reported that OVA increased the breathing resistance of the mice [11], resistive breathing induced IL-4 expression in diaphragm muscle [12], Th2 cytokines such as IL-4 and IL-13 induce iNOS expression through the STAT-6 pathway [13][14][15][16][17], iNOS reduced diaphragm muscle contraction, inhibition of iNOS induction and inhibition of NOS activity prevented diaphragm muscle contractile dysfunction [18]. Study results of ours are in agreement with study that previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…There were previously reported that OVA increased the breathing resistance of the mice [11], resistive breathing induced IL-4 expression in diaphragm muscle [12], Th2 cytokines such as IL-4 and IL-13 induce iNOS expression through the STAT-6 pathway [13][14][15][16][17], iNOS reduced diaphragm muscle contraction, inhibition of iNOS induction and inhibition of NOS activity prevented diaphragm muscle contractile dysfunction [18]. Study results of ours are in agreement with study that previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…IL-13, IL-1b, and TNF-a have been shown to induce iNOS expression in human bronchial epithelial cells, leading to elevated NO production (45,46). In addition, iNOS gene expression is regulated by the NF-kB pathway (40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in these same systems, Th2 cytokines particularly IL-4 and IL-13, inhibit iNOS expression and nitrite production, or modestly increase it in combination with IFN-g [7,[9][10][11]. Recently, IL-13 was reported to variably induce iNOS mRNA and protein expression in 2 of 3 normal human bronchial epithelial cell lines in air-liquid interface (ALI) culture, but no mechanisms for the increase were reported [12].…”
Section: Introductionmentioning
confidence: 99%